Beating-heart surgical treatment of tricuspid valve papillary fibroelastoma: A case report. Issue 34 (August 2016) - Li, Weidong; Zheng, Junnan; Zhao, Hengchi; Xu, Hongfei; Ni, Yiming
Abstract: Background: Cardiac papillary fibroelastomas are rare. And only 15% of the papillary fibroelastomas are located on tricuspid valve. However, the treatment of papillary fibroelastomas varies. Case summary: We report a 75-year-old Chinese male who was hospitalized because of a right atrial mass found by echocardiography. Complete tumor excision along with Kay's tricuspid valvuloplasty surgery on beating heart under cardiopulmonary bypass was performed to the patient. Pathologic examination confirmed the definite diagnosis of cardiac papillary fibroelastoma. The recovery of the patient was uneventful and echocardiographic examination performed 6 months after surgery revealed no recurrence of the tumor. Conclusions: Beating-heart surgical excision is an effective and safe treatment of tricuspid papillary fibroelastomas.